The nominalized infinitive in French: structure and change - Sleeman, Petra (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Many European languages have both nominal and verbal nominalized infinitives. They differ, however, in the degree to which the nominalized infinitives possess nominal and verbal properties. In this paper, nominalized infinitives in French are analyzed. It is shown that, whereas Old French was like other Romance languages in possessing both nominal and verbal nominalized infinitives, Modern French differs parametrically from other Romance languages in not having verbal infinitives and in allowing nominal infinitives only in a scientific style of speech. An analysis is proposed, within a syntactic approach to morphology. that tries to account for the loss of the verbal properties of the nominalized infinitive in French. It is proposed that the loss results from a change in word order (the loss of the OV word order in favor of the VO word order) and a change in the morphological analysis of the nominalized infinitive: instead of a zero suffix analysis, a derivational analysis was adopted by the speakers of French. It is argued that the derivational analysis restricted nominalization to Vo, which made nominalization of infinitives less ìverbalî than in other Romance languages.